Collective Forms of Work in Conversation Classes in the Course of Russian as a Foreign Language - L. U., Rajabova (Research Parks Publishing LLC, 2022)
This article is devoted to collective forms of work at Russian as a foreign language conversation classes and productive use of learning motivation, its importance and topicality.